2019
DOI: 10.1101/523522
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Probing Neural Networks for Dynamic Switches of Communication Pathways

Abstract: Dynamic communication and routing play important roles in the human brain to facilitate flexibility in task solving and thought processes. Here, we present a network perturbation methodology that allows to investigate dynamic switching between different network pathways based on phase offsets between two external oscillatory drivers. We apply this method in a computational model of the human connectome with delay-coupled neural masses. To analyze dynamic switching of pathways, we define four new metrics that m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…We have found that ephaptic coupling can decrease delays by up to 10ms, which would be one half of the period of a gamma cycle at 50Hz. It has been demonstrated that delays are critical in shaping the functional architecture of the brain [45][46][47], and ephaptic modulation of such delays could therefore play a role in flexibly synchronising distant brain areas.…”
Section: Discussionmentioning
confidence: 99%
“…We have found that ephaptic coupling can decrease delays by up to 10ms, which would be one half of the period of a gamma cycle at 50Hz. It has been demonstrated that delays are critical in shaping the functional architecture of the brain [45][46][47], and ephaptic modulation of such delays could therefore play a role in flexibly synchronising distant brain areas.…”
Section: Discussionmentioning
confidence: 99%